Palladism and the Papacy: An Episode of French Anticlericalism in the Nineteenth Century - Jones, W. R. (A journal of church and state, 1970)
W. R. Jones; Palladism and the Papacy: An Episode of French Anticlericalism in the Nineteenth Century, Journal of Church and State, Volume 12, Issue 3, 1 Octobe